Construction of coaxial ZnSe/ZnO p–n junctions and their photovoltaic applications. (21st January 2016) - Zhang, Xiwei; Meng, Dan; Hu, Dan; Tang, Zhenjie; Niu, Xiaoping; Yu, Fengjun; Ju, Lin
Abstract: Coaxial ZnSe/ZnO nanostructures were fabricated by coating a ZnO thin film on the surface of presynthesized p-type ZnSe 1D nanostructures by a sputtering method. Owing to the n-type behavior of ZnO resulting from intrinsic defects, coaxial ZnSe/ZnO p–n junctions were realized and showed a pronounced rectifying behavior. Photovoltaic devices based on the coaxial ZnSe/ZnO p–n junction showed a power conversion efficiency of 1.24% and a large open-circuit voltage of 0.87 V under UV light. The large bandgaps of ZnSe and ZnO and the high quality of the ZnSe/ZnO interface were considered to be related to the high performance of the devices.